Greenhouse Gas Emissions Efficiency in Polish Agriculture - Natalia Genstwa; Jagoda Zmyślona (Agriculture, 2023)
Analysis of the efficiency of greenhouse gas emissions in agriculture is an important part of agricultural and environmental economics research. The theme is extremely important due to the deepening problem of climate change and the simultaneous need to ensure food security. However, counteracting climate change cannot be achieved at the expense of reducing agricultural productivity. Due to the need to study the economic-environmental relationship in agriculture, the main purpose of this study was to assess the changes in the level and structure of agricultural greenhouse gas emissions and to examine the changes in efficiency of agricultural greenhouse gas emissions. The authors also estimated the relative efficiency of emissions, which allowed for comparing the efficiency of emissions between agriculture and other sectors of the national economy. Analyzing the changes in agricultural emissions efficiency, as well as changes in relative efficiency of emissions, is an indirect way of assessing whether the ongoing trends are consistent with the sustainable development concept and if the country is effective enough in mitigating climate change in relation to its economic performance. The research conducted showed that agriculture has a significant share of greenhouse gas emissions among all sectors of the Polish economy. However, greenhouse gas emissions from agriculture decreased by a total of 23.5% in the years studied. The most significant changes occurred in the context of greenhouse gas emissions from intestinal fermentation. The research also shows that the efficiency of emissions from agriculture more than doubled in the years examined. However, it decreased compared to other sectors of the economy in the country. This study was based on emissions data retrieved from National Inventory Reports prepared by the National Center for Emissions Management and on the Agricultural Statistical Yearbooks of the Central Statistical Office. This paper also proposes some examples of measures that could be taken to reduce agricultural emissions. Some of them include reducing food losses, sustainable use of fertilizers, increasing energy efficiency, and greater use of renewable energy.